Aspectos da História dos Jardins Botânicos no Mundo e no Brasil - uma Abordagem sobre o Jardim Botânico do Recife - PE - Almeida, Erika Audet de; Carneiro, Ana Rita de Sá; Alves, Marccus Vinícius (Paisagem e Ambiente, 1999)
As an essential elem ent for the conservation of living resources considering the sustainable developm ent approach on urban environm ent, the botanic garden is also a pole of high value and a facilitator in producing an environm ental awareness w hen used as an educative and scientific research instrument, and also as a tourist attractive. The purpose of this paper is to study historical aspects of the botanic gardens in the w orld and in Brazil, and how important they are in the cities developm ent. A major em phasy to Recife's Botanic Garden w as pointed out. Its localization inside of one of the Municipal Conservation area characterized for survived Atlantic Forest, should be considered specially in the city planning